Sistem Internet Hotspot Berbasis Limitasi Bandwidth dengan Fair Usage Policy (FUP) menggunakan Mikrotik : Studi Kasus: Oey Alycia Resto dan Cafe - Muhamad Sandi Pratama; Nizirwan Anwar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
This research is motivated by the problem of uneven bandwidth distribution in hotspot internet services at Oey Alycia Resto & Cafe, which negatively affects connection quality for users. The purpose of this study is to design and implement a bandwidth limitation-based hotspot internet system by applying a Fair Usage Policy (FUP) using Mikrotik devices, in order to achieve fair and efficient internet access distribution. The research method includes network requirement analysis, network topology design, Mikrotik RouterOS configuration, and system performance testing through direct observation and user questionnaires. The system implementation involves hotspot user authentication, per-user bandwidth allocation, and automatic speed reduction when data usage exceeds the predefined FUP threshold. The results show that the implemented system effectively limits excessive bandwidth usage by individual users, improves network stability, and ensures equitable internet access for all hotspot users. Furthermore, questionnaire results indicate positive user responses regarding improved internet service quality after the application of FUP. This research implies that the proposed system enhances the effectiveness of hotspot bandwidth management and can serve as a practical solution for public network administrators in optimizing bandwidth usage in a fair and controlled manner.